EXISTING SECURITY PROTOCOLS IN CFS (Information systems and technologies security, 2025)
B a c k g r o u n d . Cyber-Physical Systems (CPS) play an important role in today's technology, as they combine physical objects and cryptographic security mechanisms to ensure the secure operation of networked devices, particularly in the financial industry, the Internet of Things (IoT), and the Industrial Internet of Things (IIoT). The main problem of such systems is to ensure reliable and effective data protection with limited resources of computing power and energy consumption. Cryptographic protocols used in cyber-physical systems must be highly efficient, because both the security and the overall performance of the systems depend on their operation. This article is aimed at researching ways to improve the efficiency of cryptographic protocols in KFS.R e s u l t s . During the research, it was established that: the use of MTLS protocols increases the level of data protection, but at the same time requires a much larger amount of CFS resources compared to TLS and SSL. At the same time, TLS still uses more capacity of cyber-physical systems than SSL, which increases the cost of CFS devices. Optimizing encryption and decryption algorithms in the TLS protocol can help reduce device costs and increase data transfer speeds.C o n c l u s i o n s The obtained results show that increasing the efficiency of cryptographic protocols in cyber-physical systems is possible by using more effective encryption algorithms. Optimizing security protocols can significantly improve the data transfer rate and performance of cyber-physical systems, especially in resource-constrained environments. It is worth paying attention to the concept of using existing security protocols that combine the use of symmetric and asymmetric encryption algorithms. In the future, it is the speed of encryption and decryption that will play a significant role in increasing efficiency. Since it is this factor that will reduce the use of resources in the CFS and will also gain an advantage in time, due to the transfer of more information per unit of time, with almost no loss in crypto-resistance. Further research may focus on the development.
Keywords: cyberphysical system; asymmetric algorithm; symmetric algorithm; security protocol